Soil Liquefaction during the 20 May 2012 M5.9 Emilia Earthquake, Northern Italy: Field Reconnaissance and Post-Event Assessment. Issue 4 (November 2015) - Lai, Carlo G.; Bozzoni, Francesca; Mangriotis, Maria-Daphne; Martinelli, Mario
On 20 May 2012, a M5.9 earthquake hit the Emilia-Romagna region in northern Italy. Although it was of moderate magnitude, the quake affected an area up to 17 km from the epicenter, with severe damage and the collapse of several warehouses. Widespread liquefaction phenomena, such as sand boils and ground failures, were observed. Presented herein are the outcomes of a geotechnical post-earthquake reconnaissance survey conducted a week after the main shock in Sant'Agostino, a municipality near Ferrara, which was severely affected by the ground shaking. The presented findings add new liquefaction case records induced by a moderate earthquake in the Italian historical database. Non-invasive, seismic geophysical tests were carried out at four sites in the area of Sant'Agostino during the post-earthquake reconnaissance survey for near-surface geotechnical characterization. Preliminary assessment of liquefaction susceptibility has been carried out using post-earthquake field measurements at the four sites. Predictions based on standard, state of the practice empirical correlations are consistent with the observed liquefaction phenomena.